Detecting and mitigating robotic cyber security risks - Kumar, Raghvendra 1987-; Pattnaik, Prasant Kumar 1969-; Pandey, Priyanka (IGI Global, Disseminator of Knowledge, 2017)
"[This book] is an essential reference publication for the latest research on new methodologies and applications in the areas of robotic and digital security. Featuring extensive coverage on a broad range of topics, such as authentication techniques, cloud security, and mobile robotics, this book is ideally designed for students, researchers, scientists, and engineers seeking current research on methods, models, and implementations of optimized security in digital contexts" - Provided by publisher
Keywords: Cloud computing / Security measures; Mobile computing / Security measures; Robots / Control systems / Security measures; Computersicherheit; Roboter